Pengaruh Pijat Perineum terhadap Ruptur Perineum pada Ibu Hamil Trimester III di Klinik Penawar Bidan Yulidina Kabupaten Aceh Tengah Tahun 2022 - Katijah Katijah; Mahateara Mahateara; Kismiasih Adethia; Siska Suci Triana Ginting; Lidya Sinuhaji (PPNI UNIMMAN, 2023)
Perineal rupture is a common complication of normal delivery, especially in primigravida mothers, which can cause postpartum hemorrhage and increase the risk of maternal morbidity. One non-pharmacological method that can be used to prevent perineal rupture is perineal massage, which functions to soften the pelvic floor muscle tissue and increase the elasticity of the birth canal. This study aims to analyze the effect of perineal massage on the incidence of perineal rupture in third-trimester pregnant women. This type of research is quantitative with a Quasi Experiment design using a post-test only approach with a control group design. The study was conducted at the Penawar Bidan Yulidina Clinic, Central Aceh Regency from April to June 2022 with a sample of 30 third-trimester pregnant women divided into two groups, namely the intervention group and the control group. Data analysis used the Mann Whitney test with a 95% confidence level. The results showed a p-value = 0.020 (p <0.05) which means there is a significant effect of perineal massage on the incidence of perineal rupture. Most mothers in the intervention group did not experience perineal rupture after routine perineal massage. These results indicate that perineal massage is effective in reducing the risk of perineal rupture and can be recommended as a preventive obstetric intervention to prepare pregnant women for a safe and comfortable delivery.